Peculiarities of the Phraseology of Mexican National Variant of Spanish Language - I. V. Guseva (Vestnik MGIMO-Universiteta)
This article focuses on some theoretical and practical problems of Mexican phraseology, its historical and cultural sources and points out the difference from Spanish idioms of Pyrenean standard. The collected language material illustrates the variability of Mexican proverbs in speech, depending of the situation of the act of communication, style and reference group of the communicating subject. The article also includes a classification of the main characteristics of Mexican phraseology, that gives a possibility to compare two national variants of Spanish: the Mexican and the Pyrenean one.